O efeito da satisfação com o pós-venda e identificação com a marca na intenção de recompra: - Cardoso, Isabela Cristina Araujo (Universidade Federal do Tocantins, 2022)
This study seeks to analyze the relationships between purchase intention, brand identification and satisfaction with after sales in a refrigeration company. The participants were 35 clients of the company in the city of Araguaína-TO. As an instrument for data collection was used a self report questionnaire consists of four scales that measured the variables of the research. This study aimed to present, interpret and discuss the relationships between variables, but also test the hypotheses regarding the proposed conceptual framework, through a cross-cutting research with a quantitative approach, which collected data were analyzed by applying techniques parametric statistical calculations of descriptive statistics: means, standard deviations and correlations, multivariate statistical calculations: analysis of multiple linear regressions method enter (SPSS software, version 22.0). The results showed that the more familiarity with the brand, and being satisfied will generate the possibility of repurchasing the brand.